SUSTAINABLE URBAN DEVELOPMENT IN JAKARTA: PENTA-HELIX AND PUBLIC PERCEPTION ANALYSIS - Dananjaya, Ahmad Ghazy (Indonesian Journal of Spatial Planning, 2025)
This study critically analyzes the interplay between urbanization, spatial socio-economic disparities, and the effectiveness of Penta-Helix governance in Jakarta, along with their implications for urban sustainability. Employing a mixed-methods (sequential exploratory) approach, qualitative data were collected through in-depth interviews with Penta-Helix stakeholders, while quantitative data were gathered from a survey of 400 respondents. The study evaluates five key variables: inclusive spatial planning policies, public transport accessibility, urban environmental management, affordable housing availability, and public participation. Anticipated findings suggest a discrepancy between policy objectives and public perceptions, with a projected 70-85% alignment to be validated. The research outcomes are expected to provide robust empirical insights and policy recommendations to foster a more equitable and sustainable development path for Jakarta.